Penerapan Pendekatan Pendidikan Matematika Realistik (PMR) dalam Meningkatkan Hasil Belajar Matematika Tentang Debit - Mudji Rahardjo (Universitas Sebelas Maret, 2019)
This research is a Class Action Research (CAR) with the purpose to analyze theapplication of the Realistic Mathematic Education (RME) approach in increasing theMathematic learning outcome about Debit of the students of Class VI B the Elementary Schoolof Kasreman on the first Semester of the 2018/2019 year academic. The subjects of thisresearch are the students of Class VI B the Elementary School of Kasreman on the firstSemester of the 2018/2019 year academic as much as twenty children; consist of ten boys andten girls. The data resources of this research are relating with learning activities and learningoutcomes. Techniques of collecting data of this research are non test technique and testtechnique. The instruments of collecting data of this research are the sheets of observation, thecamera application on the hand phone, the individually tasks and also daily test. Technique ofanalyzing data of this research is comparative description. The procedure of this research is theKemmis and Mc Taggart’s model. This research is consisting of two cycle; First Cycle andSecond Cycle. Each cycle consists of three meetings. The results of this research are 1) theapplication of the Realistic Mathematic Education (RME) approach in the Mathematic learningabout Debit is a classically observing the films, discussing with the class and intensivelyexercises individual task, 2) the application of the Realistic Mathematic Education (RME)approach in the Mathematic learning about Debitis observing different films in each meetingwhich its function as concrete and interesting learning media, 3) the applications of theRealistic Mathematic Education (RME) approach in the Mathematic learning about Debit areincreasing the learning activities; focus in observing the films, very actively answering thequestions form the teacher and other students and very actively asking the questions to theteacher, 4) the applications of the Realistic Mathematic Education (RME) approach in theMathematic learning about Debit are increasing for the learning outcomes. The learningoutcomes on the Early Condition are 57,5 for the average and 45% for the completeness. Thelearning outcomes on the First Cycle are 71 for the average and 65% for the completeness. Thelearning outcomes on the Second Cycle are 82 for the average and 85% for the completeness.